Promoting socio-economic goal through government procurement: the case of South Africa and Malaysia - Abdul Rahman, Nasarudin; Wan Zahari, Wan Mohd Zulhafiz; Ahamat, Haniff; Abd Ghadas, Zuhairah Ariff (2018)
It is widely accepted that the main objective of government procurement is to maximize economic efficiency, namely, the selection of the lowest possible bid and the achievement of the best value for money. The government or its agencies are responsible to ensure that the purchasing activities will benefit the public as most of these activities are funded from taxpayers’ money. However, in some countries government procurement policy also pursues broader socio-economic objectives such as promoting equity, the growth of small and medium enterprises, the development of local industries etc. The paper aims to study the government procurement regime in two different jurisdictions, namely Malaysia and South Africa. The main focus of the study is to explore the extent to which the government procurement in these two countries is used as a vehicle to promote socio-economic policy that is to address past economic imbalances. This paper argues inter alia that the use of government procurement as a social tool should be accompanied with measures that are targeted, measurable and able to monitor for compliance. Those measures should also be implemented in a transparent and competitive manner in order to reach the ultimate objective, that is, the to achieve the best value for money the government procurement activities.